Perspektiven der räumlichen Planung: Festschrift für Gerd Hager - Kirchberg, Christian, FAVerwR; Wilske, Sebastian (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The contributions delivered to the "Große Regionalplaner-Tagung 2022" by the responsible minister of Baden-Württemberg and her staff as well as by planners and planning law experts have raised awareness of the topicality and significance of the relevant problems of spatial planning as well as state and regional planning. At the same time, Prof. Dr. Gerd Hager, Director of the Regional Association Mittlerer Oberrhein and author of the currently published 2nd edition of his commentary on the state planning law of Baden-Württemberg, has been honored in the sense of a commemorative publication on the occasion of his retirement. With contributions byProf. Dr. Susan Grotefels | RA Dr. Dirk Herrmann, FAVerwR | Constanze Martina Hinzen | Karl Heinz Hoffmann | RA Prof. Dr. Christian Kirchberg, FAVerwR | Dr. Boas Kümper | Martin Orth | RRat a.D. Prof. Dr. Axel Priebs | Nicole Razavi, MdL | VRiVG a.D. Prof. Karl-Heinz Schlotterbeck | Prof. Dr. Walter Schönwandt | Prof. em. Dr. Bernd Scholl | RA Prof. Dr. Michael Uechtritz, FAVerwR | Prof. Dr. Joachim Vogt | Dr. Sebastian Wilske